The prevalence of lower respiratory tract infection in adults visiting Tribhuvan University Teaching Hospital - Gauchan, P; Lekhak, B; Sherchand, JB (Journal of Institute of Medicine Nepal, 2007)
Background: Respiratory conditions impose enormous burden on society. Reports indicated that the top five respiratory diseases accounted for 17.4% of all deaths and 13.3% of all Disability- Adjusted Life Years (DALYs). Also, out of total acute respiratory disease, 20-24% of deaths are accounted for by Lower Respiratory Tract Infection (LRTI). In developing countries like Nepal the need for timely diagnosis of the cases and the administration of appropriate therapy based on the antibiotic susceptibility test of the causative agents is critical. However, emergence of resistant strains may occur during antibiotic therapy, which is one of the contributing factors for the increase in the frequency of LRTI in recent years in the adult population of Nepal as well. Methods: A hospital based cross-sectional study was carried out from March 2002 to February 2003. Total 181 adults presenting with LRTI defined by a new or increasing cough, productive sputum, chest pain, fever, anorexia, haemoptysis, headaches and throat ache were enrolled with their consent. This is a prospective study which included bacteriological culture, microscopic examination and sensitivity testing of bacterial isolates invitro in Health Research laboratory following Standard Operating Procedures (SOPs). Results: Lower Respiratory Infection was found prevalent in 75 cases (41.4%).Males (61.3%) were found more at risk to LRTI than females (38.7%). LRTI was found most prevalent in 50-59 year age groups (21.3%). Altogether 15 different types of bacteria were identified majority of which were Gram-negative bacteria (72.4%). Haemophilus influenzae was the commonest isolate at 23.0%followed by Klebsiella pneumoniae (18.3%). Among Gram- positive isolates Streptococcs pneumoniae was predominant (12.7%) followed by Staphylococcus aureus (9.3%).The in vitro antibiotic susceptibility test of the isolates showed that Chloramphenicol (100%) was the most effective antibiotic against Gram-negative bacteria followed by Amikacin (79.1%) and Ciprofloxaxin (66.7%), and the least effective was Co-trimoxazole (20.6%). Similarly, for the Gram-positive bacteria Ciprofloxacin (79.2%) was the most effective antibiotic and the least effective was Co-trimoxazole. Conclusion: The study shows increasing number of respiratory pathogens resistant to antimicrobials in-use to treat the infection. Key words: LRTI, Bacteria, Antibiotic susceptibility pattern, Respiratory pathogen. The full text of this paper is available at Journal of Institute of Medicine website